Readaptation of the Vestibulo-Ocular Reflex Relieves the Mal De Debarquement Syndrome - Dai, Mingjia (Frontiers Media S.A., 2014)
The mal de debarquement syndrome (MdDS), a continuous feeling of swaying, rocking, and/or bobbing, generally follows travel on the sea. The associated symptoms cause considerable distress. The underlying neural mechanisms are unknown, and to date there have been no effective treatments for this condition. Results in monkeys and humans suggested that MdDS was caused by maladaptation of the vestibulo-ocular reflex (VOR) to roll of the head during rotation. We studied 24 subjects with persistent MdDS (3 males, 21 females; 19.1 ± 33 months). Physical findings included body oscillation at 0.2 Hz, oscillating vertical nystagmus when the head was rolled from side-to-side in darkness, and unilateral rotation during the Fukuda stepping test. We posited that the maladapted rocking and the physical symptoms could be diminished or extinguished by readapting the VOR. Subjects were treated by rolling the head from side-to-side while watching a rotating full-field visual stimulus. Seventeen of the 24 subjects had a complete or substantial recovery on average for approximately 1 year. Six were initially better, but the symptoms recurred. One subject did not respond to treatment. Thus, readaptation of the VOR has led to a cure or substantial improvement in 70% of the subjects with MdDS. We conclude that the adaptive processes associated with roll-while-rotating are responsible for producing MdDS, and that the symptoms can be reduced or resolved by readapting the VOR.